Anaemia under-reporting in a hospital setting in Italy. (13th November 2019) - Lucaroni, F; Morciano, L; Morucci, L; Duggento, A; Cerone, G; Ambrosone, C; Palombi, L
Abstract: Background: Anaemia is a common occurrence in the general population, affecting nearly one in three people worldwide, with peaks in the elderly and those with chronic diseases or micronutrient deficiency. If recognised, anaemia can often be treated through micronutrient administration, thus an early recognition of the disorder has a significant return in terms of Public Health and of investment. Methods: Hospitalisation records from a large sample of ordinary admissions over a year (2016) were retrospectively analysed, in order to assess the impact of hospital stay on anaemia prevalence, defined according to WHO criteria. Prevalence was estimated by both haemoglobin levels and anaemia-related description codes (ICD9CM) at discharge. Furthermore, the main diagnoses associated with loss of haemoglobin were investigated, using binary logistic regression. Results: Over the 15, 624 ordinary admissions, we found the prevalence rate of anaemia was 47.2% at hospital admission, increasing to 63.9% at discharge. During hospital stay, a mean reduction of 0.323 g/dl (SD ± 1.39) haemoglobin was recorded, in particular those with neurological, circulatory, and haematological diseases (p < 0.001). By comparing the two diagnostic criteria, a great under-reporting occurred in 85.3% patients with haemoglobin levels predictive for anaemia at hospital discharge. Conclusions: Our results highlight the importance of correctly identifying anaemia in the hospital setting as a main Public Health concern. Since haemoglobin loss is recorded during hospital stay, we propose measuring haemoglobin levels not only at admission, but also at discharge, and to enhance proper ICD9CM code inclusion in discharge records. The achievement of both these good practices would have a double effect: to properly inform all the stakeholders and to allow more than half hospital patients, those with haemoglobin levels predictive for anaemia but without specific ICD9CM code at discharge, to be cured in the proper setting. Key messages: Anaemia often remained misidentified during hospitalisation, thus inducing a decrease in mean inpatients haemoglobin levels and a consequent increase of anaemia prevalence at discharge. Despite this worsening during hospital stay, a significant underreporting was recorded: 85.3% patients with Hb levels predictive for anaemia at hospital discharge had no specific ICD9CM code.